Development of Joomla based Website for Mapping and Location Information of Waste Disposal Sites in Palembang - Wibagso, Stefanus Setyo; Adi, Steven (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Waste is a problem that occurs in many areas. Palembang City is no exception, which will contribute 1,180 tons of waste per day in 2023. One solution that can be offered to reduce the amount of waste scattered around is the existence of a website that provides map information and the location of Temporary Waste Disposal Sites (TPS). This website facilitates the retrieval of information regarding local waste disposal sites, enabling individuals to locate them swiftly and effortlessly, thus promoting the proper disposal of waste at designated areas. For website development, researchers will use CMS Joomla and the Phoca Maps extension. The design stages adopt RAD methodology consisting of requirement planning, user design, construction, and cutover. In the functionality assessment, accurate results were achieved for Map Search and locations categorized by Specific Area Categories and TPS Names. The results obtained from this research are that the website provides information on maps and TPS locations. Joomla CMS, along with the Phoca Maps extension, offers benefits in terms of convenience, affordability, and ease of managing maps and location markers. Additionally, this study presents an alternative perspective on the use of Joomla CMS, which is typically associated with text or image content usage.